THE ARGOLIS PENINSULA IN THE PALAEOGEOGRAPHIC AND GEODYNAMIC FRAME OF THE HELLENIDES - Bortolotti, Valerio; Carras, Nicolas; Chiari, Marco; Fazzuoli, Milvio; Marcucci, Marta; Photiades, Adonis; Principi, Gianfranco (Ofioliti, 2003)
Geological and biochronological studies on the Argolis Peninsula (Pelagonian - Subpelagonian Domain) -also based on petrological data on the ophiolitic rocks- allowed us to propose a new tectonic unit succession; from the bottom upwards: a- the Trapezona Unit (Early-Middle Triassic - Late Jurassic; Pelagonian continental margin); b- the Dhimaina Ophiolitic Unit (Middle Triassic-Late Jurassic/Early Cretaceous oceanic realm, covered by an Early Cretaceous- Eocene “Mesautochthon; c- the Iliokastron Mélange Unit (Middle-Late Jurassic - Early Cretaceous) in the northern Argolis and the Adheres Melange Unit (Cretaceous-Paleocene) in the southern Argolis; d- the Faniskos Unit (Late Jurassic-Eocene).Based on a close examination of the paleogeography of the continental margin successions and of their possible relationships with the ocean floor successions, we propose a model for the evolution of the oceanic and continental domains of this section of the Hellenides during the Triassic-Eocene interval, and we try to frame it into the evolution of the whole Dinaric-Hellenic orogenic system. This model hypothesises the opening, during Middle-Late Triassic time, of a single ocean in the Dinaric-Hellenic realm (the Vardar Ocean), which continues its spreading phase until the Middle Jurassic when, an intra-oceanic subduction zone, testified by the presence of IAT volcanites and boninitic rocks developed contemporaneously with MOR basalts. During the Late Jurassic obduction of the ophiolitic units onto the continental margin began. During the Early Cretaceous, the complete thrusting of the Dhimaina Ophiolitic Unit onto the Trapezona Unit occurred. During Eocene, and particularly after the Ypresian, the different units reached their present tectonic setting.